Urbanization altered latitudinal patterns of bird diversity-environment relationships in the southern Neotropics - Filloy, Julieta (2015)
Given the global expansion of urbanization, it is crucial for planning to understand how that process affects spatial patterns of diversity. At broad geographical scales, climatic conditions such as temperature or rainfall usually explain those patterns. Our objective was to analyze and compare the species richness-environment relationships and the distance decay in similarity of bird communities between urban centres and less intensively modified adjacent rural areas along a latitudinal gradient in the southern Neotropics. We surveyed birds in 15 urban centres and their adjacent rural areas from 26° to 38°S and compiled temperature and rainfall data. We performed regression analyses and Mantel tests to explore latitudinal changes in bird species richness and taxonomic composition as a response to those climatic variables in urban centres and in rural areas. Results showed that species richness decreased with latitude in rural areas, and temperature and rainfall accounted for that decline, but remained relatively constant in urban centres. The difference in species richness between urban centres and rural areas was larger at lower latitudes. Similarity in the composition of bird assemblages declined with distance at a similar rate in both urban centres and rural areas; however, similarity was higher between urban centres than in rural areas at any given distance. Environmental differences due to temperature and rainfall partially accounted for the distance decay in similarity for both urban and rural areas. The impact of urbanization on bird species richness seems to differ according to the climatic context in which urbanization develops, and it is expected to be higher in tropical than in more arid environments. Our study remarks the importance of considering urban systems as components of larger ecological systems.